(2x-4)(5x+7)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

2x-4=0

5x+7=0

Set the first factor equal to 0.

2x-4=0

Add 4 to both sides of the equation.

2x=4

Divide each term by 2 and simplify.

Divide each term in 2x=4 by 2.

2×2=42

Cancel the common factor of 2.

Cancel the common factor.

2×2=42

Divide x by 1.

x=42

x=42

Divide 4 by 2.

x=2

x=2

x=2

Set the next factor equal to 0.

5x+7=0

Subtract 7 from both sides of the equation.

5x=-7

Divide each term by 5 and simplify.

Divide each term in 5x=-7 by 5.

5×5=-75

Cancel the common factor of 5.

Cancel the common factor.

5×5=-75

Divide x by 1.

x=-75

x=-75

Move the negative in front of the fraction.

x=-75

x=-75

x=-75

The final solution is all the values that make (2x-4)(5x+7)=0 true.

x=2,-75

Solve using the Square Root Property (2x-4)(5x+7)=0